The effect of vortioxetine on overall patient functioning in patients with major depressive disorder. Issue 3 (2nd February 2017) - Florea, Ioana; Loft, Henrik; Danchenko, Natalya; Rive, Benoît; Brignone, Melanie; Merikle, Elizabeth; Jacobsen, Paula L.; Sheehan, David V.
Abstract: Background: The objectives of this meta‐analysis of data from randomized, placebo‐controlled studies were to assess the effect of vortioxetine on overall functioning (primary) and functional remission (secondary) using the Sheehan Disability Scale (SDS) in adults with major depressive disorder (MDD). Methods: Data from nine short‐term (6/8 weeks) pivotal studies that included patient functioning assessments were included in this random‐effects meta‐analysis, which used aggregated study‐level data for all therapeutic vortioxetine doses and a mixed‐effect model for repeated measures using the full analysis set. Results: A total of 4, 216 patients received ≥1 dose of study treatment (1, 522 placebo, 2, 694 vortioxetine 5–20 mg/day). At study end, the meta‐analysis showed improvement for vortioxetine versus placebo ( n  = 911) in SDS total score (vortioxetine 5 mg, n  =   564, change from baseline versus placebo [Δ] −0.24, p  = NS; 10 mg, n  =   445, Δ −1.68, p  ≤   .001; 15 mg, n  =   204, Δ −0.91, p  = NS; 20 mg, n  =   340, Δ −1.94, p  ≤   .01). Functional remission (SDS total score ≤6) was observed with vortioxetine 10 mg ( n  =   170/573; odds ratio [OR] relative to placebo 1.7, p  <   .001) and 20 mg ( n  =   144/447; OR 1.6, p  <   .05), but not 5 mg ( n  =   207/757; OR 1.1, p  = NS) or 15 mg ( n  =   92/295; OR 1.3, p  = NS). Conclusion: Vortioxetine 5–20 mg for 6/8 weeks improved overall patient functioning in patients with MDD. Relative to placebo, vortioxetine 10 and 20 mg demonstrated significant improvement in SDS total score and functional remission. Abstract : This meta‐analysis evaluates the effect of vortioxetine 5–20 mg/day versus placebo on patient functioning in major depressive disorder (MDD) patients, as measured by the Sheehan Disability Scale, with additional analyses conducted in subgroups of MDD patients with severe MDD and/or significant functional impairment, as well as in the subgroup of patients with high levels of anxiety symptoms. Vortioxetine demonstrated statistically significant improvements in patient functioning versus placebo in the total MDD population, as well as in all of the defined subgroups. Functional improvement with vortioxetine 5–20 mg/day tended to be dose‐dependent, with the exception of the 15‐mg dose.